THE ROLE OF SHADOW TEACHER IN LEARNING MANAGEMENT OF CHILDREN WITH SPECIAL NEEDS IN PAUD TERPADU INKLUSI BINA INSAN KREATIF TASIKMALAYA - Yuli Salis Hijriyani; Fenty Andriani; Rosidin Rosidin (Evaluasi: Jurnal Manajemen Pendidikan Islam, 2021)
As part of inclusion education, Education for All (EfA) or Pendidikan untuk Semua (PuS) has six main programs, including the inclusion program of Early Childhood Education (Pendidikan Anak Usia Dini or PAUD). This article is compiled based on a qualitative approach, which is a type of field research and presented descriptively. This article highlights the role of Shadow Teacher as one of the main keys to the success of inclusion education in PAUD Terpadu Inklusi Bina Insan Kreatif (BIK) in Tasikmalaya city. The findings of the article show that Shadow Teacher has a variety of relatively different roles and responsibilities than class teachers. But it plays a big role in helping the success of learning carried out by class teachers, especially related to Children with Special Needs (Anak Berkebutuhan Khusus or ABK). In undergoing its roles and responsibilities, Shadow Teacher applies various strategies to assist the development of ABK students, in the academic, non-academic and self-developed fields. Furthermore, the PAUD Terpadu Inklusi BIK institute has such a crucial policy related to improving the quality, qualifications and competency of Shadow Teacher that it can provide better inclusion education services for ABK students in particular, and for other stakeholders in general.